(untitled) (Indian Journal of Nematology, 2024)
The experiment was conducted in kharif and rabi seasons using okra and chickpea, respectively to test the efficacy of Pasteuria penetrans as seed treatment against Meloidogyne javanica. The results on chickpea were not significant. However, only during kharif season (mean maximum and minimum temperatures of 34.5 and 26.4° C, respectively) on okra, P. penetrans used @ 4 and 5% as seed coat resulted in significant reduction in root galling, egg production and infection of females.